Adjustable ergonomic sewing machine workstation for Filipino small-scale industry operators - Alonto, Akhzanuniza "Honey" M.
One of our basic neccessities in life is clothing.In the process of making clothes, shoes, apparels and such, the most widely used means to do so is the sewing machine. There are numerous ways in the industry to cater to these needs, which vary from the large scale manufacturers down to the small scale businesses. There are also sewing machine operators who use the sewing machine for their hobbies. Nevertheless, despite the fact that different types of sewing machines and workstations are utilized at home and at work, there is not much consideration or very little attention given to the ergonomic factors for the workstation especially in the work place. Although there are others who have undergone studies on the lack of ergonomics design of the sewing machine workstation, the researcher felt the need to research on the need for a more anthropometrically correct standard of measurement of sewing machine workstations for the comfort of Filipino operators, specifically in the small-scale industry.